Evaluating the persistence of malachite green residues in tilapia and pacu fish - de Freitas, Lucas Victor Pereira; Silveira, Juliana Grell Fernandes; Damaceno, Marina Alves; Campanharo, Sarah Chagas; da Silva, Agnaldo Fernando Baldo; Jonas Joaquim Mangabeira, da Silva; Portela, Ana Carolina Vellosa; de Jesus, Raphael Barbetta [UNESP]; Sasanya, James Jacob; Pilarski, Fabiana [UNESP]; Rath, Susanne; Paschoal, Jonas Augusto Rizzato (Elsevier, 2024)
Although banned in food-producing animals, residues of malachite green (MG) and its primary metabolite, leucomalachite green (LMG), have been found in fish due to illegal use in aquaculture and the release of industrial wastewater, which represent a serious risk to food and environmental securities. This study aimed to investigate the residue depletion profile of MG and LMG in edible tissues of Nile tilapia (Oreochromis niloticus) and pacu (Piaractus mesopotamicus) cultured simultaneously under the same environmental conditions to support control measures in case of abuse. An analytical method involving QuEChERS sample preparation and liquid chromatography coupled to tandem mass spectrometry was developed, validated, and applied to quantify MG and LMG residues in fish fillets from two depletion experiments after treatment by immersion bath (MG at 0.10 mg L-1 for 60 min). During the experiment, the average water temperature was 30 ºC, while the pH was 6.9. The method is selective, precise (CV = 0.4 - 22%) and accurate (recovery 92 - 114%). The limits of detection and quantification are 0.15 and 0.5 ng g-1, respectively. In both species, the sum of MG and LMG residues were quantified up to the 32nd day post-exposure, and the concentrations were significantly higher in the pacu fillets (up to 3284 ng g-1) than in Nile tilapia (up to 432 ng g-1). The sums of MG and LMG residues were below 2 ng g-1 at 44 days and 342 days for Nile tilapia and pacu, respectively – the Minimum Required Performance Limit (MRPL) for analytical methods intended to monitor forbidden substances in food according to old European Commission guidelines. The persistence of MG residues in pacu may be attributed to its higher lipid content, which favors the accumulation of the non-polar metabolite LMG. These results provide insights into the concern about human, animal, and environmental health risks resulting from unauthorized use or aquatic contamination by industrial wastewater containing MG residues.
Keywords: Aquaculture; Leucomalachite green; Malachite green; Persistence; Residue depletion